The core of religious education: Finnish student teachers’ pedagogical aims - Kuusisto, Elina (Journal of beliefs and values, 2014)
This article investigated the core of religious education (RE) by examining Finnish student teachers’ pedagogical aims in the context of Lutheran RE. The data consisted of essays (N=82) analysed in a deductive manner using the main concepts of the didactic triangle together with the aims of the Finnish National Core Curriculum. The student teachers identified familiarising oneself with one’s own and other religions in addition to growing ethically and understanding the religious dimension of life as the core goals of RE. By attaining these goals, pupils may also achieve the higher order aims of RE and cross-curricular goals of the curriculum. A teacher’s pedagogical and moral competence as well as expertise in subject matter was emphasised, and the pedagogical relation with students was also seen as important. A deeper understanding of pupils and the importance of a didactic relation in teaching were identified as pedagogical aims that need to be pursued further.